Life events in obsessive-compulsive disorder: A cross-sectional study - Subir Bhattacharjee,; Prabir Kumar Kundu,; Shatabdi Saha, (Asian Journal of Medical Sciences, 2023)
Background: Obsessive compulsive disorder (OCD) is a chronic psychiatric disorder having significant deterioration in patients’ socio-occupational functioning. Stressful life events (SLE) were noted before onset of this disorder. The previous study with Indian population found positive correlation between stressful and traumatic life events and OCD, but was with small sample size and thus result couldn’t be generalized. Aims and Objectives: The aim of the study was to examine the role of life events in patients with OCD and to find out correlation between them, if any. Materials and Methods: Consecutive 30 OPD patients fulfilling ICD-10 DCR criteria for OCD were rated with Yale Brown Obsessive Compulsive Scale (YBOCS), Hamilton Rating Scale for Depression (HAM-D), Hamilton Rating Scale for Anxiety (HAM-A), and Presumptive Stressful Life Events Scale (PSLES). A group of 30 healthy controls from unrelated patient party were also rated on PSLES. Finally, both groups were statistically compared in terms of life events. Results: Two groups were identical in distribution of age and sex. The frequency of life events, 1-year (P=0.000) and lifetime (P=0.000), were significantly higher in OCD group in comparison to healthy controls. There was significant positive correlation between PSLES scores and YBOCS scores. Step-wise linear regression analysis found positively predictability of PSLES score to OCD severity. Conclusion: OCD patients have statistically significant SLE before the onset of their disorder and total number of life events has positive correlation with severity of OCD.